2010
DOI: 10.1007/s00467-010-1583-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum RANKL, osteoprotegerin (OPG), and RANKL/OPG ratio in nephrotic children

Abstract: Receptor activator of NF-kB ligand (RANKL) and osteoprotegerin (OPG) play key roles in the pathogenesis of glucocorticoid-induced osteoporosis (GIO). The aim of our study was to determine whether the cumulative glucocorticoid dose (CGCS) in children with idiopathic nephrotic syndrome (INS) has any effect on the concentration of serum RANKL and OPG and the RANKL/OPG ratio. The study population consisted of 90 children with INS, aged 3–20 years, who were treated with GCS. These children were divided into two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
2
25
0
1
Order By: Relevance
“…We observed an approximate 2-fold increase in the RANKL/OPG ratio using serum specimens from CHIKV patients. This is similar in magnitude to the increases in RANKL/OPG ratios reported for patients with postmenopausal osteoporosis (1.8-fold) (58), osteoarthritis patients (ϳ1.5-fold) (59), and children with osteoporosis due to glucocorticoid therapy for idiopathic nephrotic syndrome (ϳ1.5-fold) (60).…”
Section: Discussionsupporting
confidence: 83%
“…We observed an approximate 2-fold increase in the RANKL/OPG ratio using serum specimens from CHIKV patients. This is similar in magnitude to the increases in RANKL/OPG ratios reported for patients with postmenopausal osteoporosis (1.8-fold) (58), osteoarthritis patients (ϳ1.5-fold) (59), and children with osteoporosis due to glucocorticoid therapy for idiopathic nephrotic syndrome (ϳ1.5-fold) (60).…”
Section: Discussionsupporting
confidence: 83%
“…Clinical research also showed that OPG levels are significantly higher in patients with chronic kidney disease (CKD) compared with age- and sex-matched controls, and increasing OPG levels have a linear relationship with adverse renal function [3639]. Elevated OPG is associated with all-cause mortality in CKD stage 4 and 5 patients in addition to vascular calcification [40].…”
Section: Discussionmentioning
confidence: 99%
“…3). An increasing RANKL/OPG ratio after fracture is considered to tilt the balance of RANKL and OPG toward bone resorptive status (17), since this balance is critically important for bone remodeling and the preservation of bone mass (23). The RANKL-OPG balance may affect osteoclast activity, which is why it has been suggested that the serum RANKL/OPG ratio is a critical factor for determining osteoclast activation (24).…”
Section: Discussionmentioning
confidence: 99%